Photo‐Assisted CO/CO2 Methanation over Ni/TiO2 Catalyst: Experiment and Density Functional Theory Calculation. Issue 17 (22nd April 2022) - Li, Yangyang; Rao, Zhiqiang; Liu, Zhisong; Zeng, Junming; Bao, Wentao; Wang, Zijun; Li, Jiangbing; Yu, Feng; Dai, Bin; Zhou, Ying
Abstract: Supported Ni‐based catalysts have been widely used in CO and CO2 methanation processes. However, the catalytic activity of presently available Ni‐supported catalysts remains deficient at the low temperatures required to avoid sintering and carbon deposition. The present work addresses these issues by fabricating TiO2 ‐nanoparticle‐supported Ni (Ni/TiO2 ) photothermal catalysts achieve a CO and CO2 conversion of 94 % and 76 %, respectively, under Xe lamp irradiation at 300 °C than those obtained under strictly thermal catalysis conditions. Diffuse reflectance infrared Fourier‐transform spectroscopy results conducted in situ with and without light irradiation demonstrate that photoinduced charge carriers on the surfaces of the Ni/TiO2 nanoparticles enhance the formation of intermediate species in the CO methanation process and the formation of CO2 δ− species conducive to CO2 activation in the CO2 methanation process. Moreover, density functional theory calculations with explicitly included charge carriers further demonstrate that electrons are transferred from Ti to Ni in the Ni/TiO2 catalyst under light irradiation. This research advances understanding of CO/CO2 low temperature methanation activity by light irradiation and provides a practical way to address the existing problem for Ni‐based catalysts. Abstract : Photo‐thermal catalyst Ni/TiO2 provides significantly increased CO and CO2 conversion under light irradiation. Photoinduced charge carriers on the surfaces of the Ni/TiO2 catalyst enhance the formation of intermediate species, reduce the activation energy barrier required for the reaction and advance performance of CO/CO2 methanation.